SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM PELAKSANAAN ADMINISTRASI GURU DENGAN MENGGUNAKAN GOOGLE WORKSPACE DI SMA FITRAH ISLAMIC WORLD ACADEMY BOGOR - Muhammad Lanri Siregar; Dewi Yanti (UNISAN JURNAL, 2024)
The principal as a supervisor must be able to control teachers to improve their performance in managing learning. Teacher administration that reflects the teaching carried out by teachers to facilitate student learning must always experience innovation. So there is a need for Google Workspace for Education innovation to improve the quality of learning. This research included qualitative research which was carried out at SMA Fitrah Islamic World Academy Bogor. The data collection techniques used in this research are through observation, interviews, documentation, and triangulation (combination). The data that has been collected is analyzed using qualitative analysis. As a result of the research, there are conclusions that are in accordance with the research focus that can be drawn from the research, namely: a) The role of the principal in implementing teacher administrative supervision at Fitrah Islamic World Academy Bogor High School. b) Implementation of teacher administrative supervision at SMA Fitrah Islamic World Academy Bogor. c) Obstacles faced in implementing teacher administrative supervision at Fitrah Islamic World Academy Bogor High School.